Challenging Gender Norms: The Representation of Princess Merida in Movie Brave - Putri, Maya Oktaviani; Prastiwi, Yeni (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2025)
Women in social structures are often depicted as feminime, as seen in Disney movies. However in the early 2010s, Disney cartoons like Brave showed a shift in the image of women. Women previously depicted in Disney movies have been portrayed as submissive, dependent and passive. Female characters in the Brave movies are portrayed as individuals in their own right, capable of leading, active and not needing men. This research aims to analyze how the film Brave challenges traditional gender roles through its portrayal of a female protagonist with traits typically associated with masculinity. This study used liberal feminism. The results of this research construct women as protagonists in the Brave movie (Princess Merida), resulting in portrayal of male characteristics, such as being strong, rational, brave, independent fighter, and able to negotiate. It is hoped that the thesis of this research will explain the importance of media for women and reference gender studies.